Enhancing smallholder maize shelling mechanization through the collective business model: the case of Northern Ghana - Ansah, I.G.K.; Kotu, B.H.; Boyubie, B.; Bonney, J.E. (Frontiers Media, 2024)
This paper assessed the conditions contributing to the success of smallholder farmer groups in northern Ghana using mechanical maize shellers (MMS) based on a collective business model. A sample of 156 farmers from 18 intervention communities was analyzed using qualitative comparative analysis (QCA) to examine the conditions necessary to increase usage of MMS. The results revealed a single configuration for achieving high group MMS usage, observed in about 24 percent of the cases. This configuration comprises five sufficient conditions: high cooperation, good relationships among members, payment of financial contributions, provision of prior notice for group meetings, and obedience to group rules. Additionally, two necessary conditions identified were low conflict and reduced use of manual maize shelling. When these core conditions coexist within the farmer groups, the MMS is more likely to be highly utilized. These findings suggest that group leaders and members should encourage mutual understanding, respect individual differences, value diverse opinions, and share responsibilities to improve cooperation, foster better relationships, and reduce conflicts among members. This approach can encourage both existing and new members to utilize the services of mechanical sheller groups, ensuring sustainability. Future research should utilize alternative econometric procedures to evaluate the configurations identified by the QCA analysis, aiming to enhance the reliability and confidence of empirical findings.